Efeito da administração de Duloxetina sobre citocinas inflamatórias e sintomas motores em pacientes com doença de Parkinson – estudo aberto - Silveira, Juliana Oliveira Freitas (2019)
Parkinsonism is a neurological syndrome characterized by resting tremor, stiffness in cogwheels, postural instability and bradykinesia. Parkinson's disease (PD) is the second most common neurodegenerative disease and the leading cause of parkinsonism, accounting for 80% of cases. It is the second most prevalent movement disorder. Neuroinflammation and the increase of serum inflammatory cytokines have been associated with the disease. As several studies have shown that antidepressant drugs decrease serum proinflammatory cytokines in animal models of PD and improve the motor symptoms of selected patients, we investigated whether adjuvant therapy with duloxetine decreases peripheral levels of inflammatory cytokines and motor symptoms in PD patients without other chronic inflammatory diseases. This open, non-randomized, non-placebo controlled clinical trial was conducted at the Santa Maria University Hospital with the objective of assessing whether 8 weeks of adjuvant therapy with duloxetine improved the Unified Parkinson's Disease Rating Scale (UPDRS), the Hoehn and Yahr modified (HY) and PDQ-39 (Parkinson Disease Quality of Life Questionnaire) in 17 patients with PD. Serum levels of tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β), interleukin 6 (IL-6) and interleukin 10 (IL-10) were determined before and after 4 and 8 weeks of pharmacological intervention. There were no withdrawals during the study. Duloxetine significantly improved motor symptoms, activities of daily living and quality of life in patients with PD. Ten patients presented a decrease of 5 points (or more) in the UPDRS scores, being arbitrarily classified as responders. The therapeutic response was predicted by the logistic regression of the clinical parameters in the recruitment, being a score of HY of at least 2 more important. While serum levels of IL-6, IL-1β and TNF-α decreased, IL-10 levels increased at the end of the pharmacological intervention. We conclude that duloxetine improves the clinical and inflammatory profile of patients with PD. We suggest that adjuvant therapy with duloxetine may bring additional benefits to selected PD patients.